PENGARUH KUALITAS LAYANAN DAN CITRA PRODUK KREDIT UMKM TERHADAP KEPUASAN SERTA LOYALITAS NASABAH KREDIT PD. BKK DEMPET - KABUPATEN DEMAK (Students' Journal of Accounting and Banking, 2013)
The research was conducted on PD BKK Dempet Demak with the aim to determine the effect of the variable quality of service and product image on customer loyalty loans either directly or mediated by customer satisfaction. Study using a sample of 100 people who were taken by purposive sampling technique. The tool uses multiple regression analysis and path analysis. Based on the results of the hypothesis test result that quality of care is not significantly affect customer satisfaction and loyalty, while the product image variable positive and significant effect on customer satisfaction and loyalty. Mediation test showed that the mediating effect of customer satisfaction and service quality on customer loyalty product image. On the basis of these results it can be recommended that advice is, that service to customers as well as efforts to build the image of SME loans can be further improved to maintain customer loyalty. Keywords : Quality of Service, Product Image, Customer Satisfaction and Customer Loyalty.